The Costumes of Topeng Panji Dance at Surakarta Palace, Indonesia: Symbolic Meanings and Functions - Fajar Nur Annisa,; Slamet Subiyantoro,; Sumarwati, (Wacana Seni Journal of Arts Discourse, 2025)
Traditional dance costumes in Indonesia, including those used in Topeng Panji dance at Surakarta Palace, carry symbolic meanings and functions that reflect educational characters. However, these meanings and functions are only known within a limited circle, primarily within the palace, making them unfamiliar to the public. This study aims to describe the symbolic meanings and functions of Topeng Panji dance costumes at Surakarta Palace in Indonesia. This qualitative research involved participants from the Surakarta Palace family, cultural experts, and the creators and main dancers of the Topeng Panji dance. Data were collected through observations and supported by information from informants as well as documentation in the form of photographs, videos, and books related to the dance. The data were analysed qualitatively using content analysis. The results of the study revealed: (1) the symbolic meanings of the costumes include representing power and status within the kingdom, distinguishing between protagonist and antagonist characters, symbolising readiness for war, and functioning as a weapon of war; and (2) the functions of the costumes include character depiction, character enhancement, and serving as a medium to facilitate movement. Audiences respond to the costumes’ appearance through their five senses, engaging imagination and emotion. The symbolic meanings of the Topeng Panji dance costumes hold educational value and should be studied further as a learning material for the wider community.